Clinical impact of SARS-CoV-2 infection among patients with vulvar cancer: the Gemelli Vul.Can multidisciplinary team. Issue 2 (13th December 2021) - Federico, Alex; Fragomeni, Simona Maria; Tagliaferri, Luca; Guajardo Rios, Linda Stella; Lancellotta, Valentina; Gentileschi, Stefano; Corrado, Giacomo; Gui, Benedetta; Colloca, Giuseppe; Rufini, Vittoria; Fagotti, Anna; Scambia, Giovanni; et al.
Abstract : Background: 'Severe acute respiratory syndrome coronavirus-2' (SARS-CoV-2) infection has dramatically affected the management of patients with cancer, who are most vulnerable to the consequences of the infection. Patients with vulvar cancer are frequently elderly and affected by multiple co-morbidities, thus representing a particularly frail population. Objective: To assess the clinical impact of the SARS-CoV-2 infection among patients scheduled for treatment for active vulvar cancer. Methods: Data on patients with vulvar tumors referred to Fondazione Policlinico Universitario Agostino Gemelli IRCCS between February 2020 and July 2021 were retrospectively analyzed. Patients with a positive reverse transcription polymerase chain reaction in nasopharyngeal swab were considered as positive for SARS-Cov-2. Results: One hundred and ninety-one patients with vulvar cancer were evaluated and scheduled for treatment. The median age was 72 years (range 35–94). Seven (3.7%) patients were diagnosed with SARS-Cov-2 infection: three (42.9%) had their treatment delayed, with no apparent consequences, two (28.6%) had their treatment delayed and later abandoned because of clinical worsening due to oncologic disease progression, and two (28.6%) contracted the infection in the post-operative period and died due to respiratory complications. Conclusions: In most cases the infection had major clinical implications, being associated with significant delays in oncologic treatments and extremely high mortality when contracted in the post-operative period.